Hydrochemical variation characteristics and driving factors of surface water in arid Areas—a case study of Beichuan River in Northwest China - Jinbing, Xing; Long, Wang; Jie, Zhao; Tianlun, Zhai (Frontiers in Environmental Science, 2024)
This study investigates the hydrochemical characteristics and driving factors of the Beichuan River in the arid region of Northwest China. Surface water samples were collected during wet and dry seasons, and analyzed using hydrochemical diagrams, mathematical statistics, and principal component analysis (PCA). The results show that the pH value of Beichuan River is generally weakly alkaline, the main hydrochemical types are HCO3-Ca, and the average TDS are 224mg/L and 236mg/L respectively, which are higher than the world average level (115mg/L). The seasonal variation of hydrochemical components is mainly controlled by rainfall, showing that the concentrations of Na + , Cl -and NO3 -in the wet season are higher than those in the dry season, while the concentrations of other chemical components show an opposite trend, while the spatial variation is mainly controlled by human activities, and the concentrations of hydrochemical components show a gradual increasing trend from upstream to downstream, especially Na + , Mg 2+ , Cl -and NO3 -. Rock weathering is the key natural factor controlling the Hydrochemical Composition of Beichuan River. Na + and Cl -are mainly from the dissolution of silicate, Ca 2+ and Mg 2+ are mainly from the weathering of carbonate rocks and silicate, and SO4 2-is mainly from the dissolution of evaporite. It is noted that human activities, especially domestic sewage and agricultural runoff, contribute significantly to NO3 -in the water body. PCA identified rock weathering and agricultural runoff as major wet-season factors, while domestic sewage predominantly affects the dry season.This study can provide a scientific basis for the rational development of water resources and ecological environment protection in arid areas.